Needs for processing career promotion course to add value for freshwater fish farmers in Nakhon Sawan Province. - Jamree Khrueahong; Pakkapong Poungsuk; P. Junlex (International Journal of Agricultural Technology, 2025)
Results revealed that the respondents needed training courses for fish crackers, dried fish strips, sour pickled fish, fish sausage, and fermented fish. They needed a 1-2 days training course at the training place in the village during the off-season for rice growing. The participants should be around 21-30 persons and the training program that informed at least one week in advance. Training activities should focus on actual practice (91.50%) and the training organizer must be responsible for expenses (99.02%). Each time of the training should have only one topic ( = 3.55; S.D = 1.08). Assessment through observation during the training should be done ( = = 3.77; S.D. = 0.58) and assessment after the training must be conducted ( =3.75, S.D. = 0.79), For the training session, it should include demonstration ( = 4.23, S.D. = 0.67) actual practice ( = 4.40, S.D. = 0.61) and diverse use of media ( = 4.29, S.D. = 0.68). According to the comparison, there was a statistical difference between the needs for training and the socio-economic attributes of the respondents. The latter included sex, educational attainment, farmer group membership, number of household labor, and debts or sources of loans. A training course for value-added processing of freshwater fish has tended to develop for future training sessions with farmers.
Keywords: Agricultural Economics and Practices; Livestock Management and Performance Improvement; Fisheries and Aquaculture Studies